The Effect of Interactive PPT-Based Learning Media with a Contextual Approach on Student Learning Interest in Statistics Material in Class X SMA - Sibarani, Mikhael Agus Tua; Tumanggor, Abednego; Tarigan, Adelia Br; Silvina, Nur; Banjarnahor, Tohom Paha Mei; Henniwati; Kairuddin (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2025)
The education sector plays a vital function in producing a flexible, innovative and internationally competitive workforce. However, the teaching of arithmetic still experiences obstacles, especially in fostering students' interest in topics that are considered theoretical such as statistics. This research was conducted to analyze the impact of using interactive PowerPoint-based learning media with a contextual approach on students' interest in learning statistics. This research applies quantitative methods with the subject of X-level students at SMA Negeri 1 Deli Tua. Data analysis procedures included normality testing, homogeneity of variance testing, t-test, simple linear regression analysis, and coefficient of determination testing. The research findings showed that contextualized intera ctive PowerPoint media had a positive impact on students' interest in learning. Through regression analysis, it was identified that the increase in students' positive responses to the learning media was directly proportional to the increase in interest in learning. Testing the coefficient of determination showed a figure of 40.66%, indicating that the variable of students' responses to the media contributed 40.66% to learning interest, while the other part was influenced by external factors outside the model.